2020
DOI: 10.31487/j.scr.2020.02.03
|View full text |Cite
|
Sign up to set email alerts
|

Complicated Abdominal Seat Belt Injuries in Children

Abstract: Background: The proper use of security accessories in cars has resulted in the reduction of morbidity and mortality both in adults and children. Improper use of abdominal seat belt is associated in some cases with severe abdominal injuries. Objectives: Investigation of the treatment outcomes of children who suffered complicated abdominal seat belt injuries between 1998 and 2013. Methods: We present five cases of children aged 6-14 years, who suffered complicated abdominal injuries due to improper use of the se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 8 publications
0
1
0
Order By: Relevance
“…The presented data provide a hint, that pelvic, abdominal, and thoracic injuries could be indicators for even more severe injuries e.g., TBI or spinal injuries. Sweed et al (JAHR) showed in their case reports, that rare injuries, e.g., abdominal aortic injury, can easily be missed initially [34]. Although abdominal aortic trauma was associated with duodenal injuries in almost all described cases it still seems to be a rare event and was not found in the present dataset of the TR-DGU.…”
Section: Discussionmentioning
confidence: 60%
“…The presented data provide a hint, that pelvic, abdominal, and thoracic injuries could be indicators for even more severe injuries e.g., TBI or spinal injuries. Sweed et al (JAHR) showed in their case reports, that rare injuries, e.g., abdominal aortic injury, can easily be missed initially [34]. Although abdominal aortic trauma was associated with duodenal injuries in almost all described cases it still seems to be a rare event and was not found in the present dataset of the TR-DGU.…”
Section: Discussionmentioning
confidence: 60%